LEXICALIZATION IN MORPHOLOGY: A CASE STUDY OF THE ANTICAUSATIVE PREFIX IN TAQBAYLIT BERBER - Amazigh Bedar (Studii de gramatică contrastivă)
What makes lexicalization an intriguing topic in morphology? It is not so much the semantic mismatch between a base and its ‘derived’ form, but the question of how lexicalization is underlyingly represented. This paper explores this question with a case study of the anticausative morpheme in Taqbaylit Berber. Although this prefix, namely /n-/, has the status of a derivational morpheme, it is lexicalized in a series of verbs. A morphophonological analysis will be provided, certain points on the argument structure of this series of verbs will be discussed, and it will be shown that this former morpheme is no longer realized as a prefix but incorporated into the root and became the first root consonant. Specifically, it will be argued that this prefix has lost its morphemic status and therefore is devoid of any functional or categorial information.